2010
DOI: 10.1108/00251741011068815
|View full text |Cite
|
Sign up to set email alerts
|

Corporate mission, corporate policies and business outcomes: evidence from Japan

Abstract: Purpose -This study sets out to explore questions such as: "Does mission statement matter? If so, in what ways?" Using data on mission statements of 128 large Japanese firms, the paper aims to show that corporate mission has a significant impact on corporate policies that determine employment, board, and financial structures. Design/methodology/approach -The paper provides evidence that strong-mission firms are more likely to retain incumbent employees, promote managers from within firms, and have less debt an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 56 publications
1
53
0
2
Order By: Relevance
“…The improved performance of the employees leads to better use of the company's assets and equity, thereby increasing productivity and optimizing the ROA and ROE. This result is in line with results from previous studies on the relationship between MSs and ROA (Bart 1997b, Bartkus et al 2006, Hirota et al 2010. As for the relationship between MSs and ROE, to the best of the authors' knowledge, this is the first study to analyze this relationship.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The improved performance of the employees leads to better use of the company's assets and equity, thereby increasing productivity and optimizing the ROA and ROE. This result is in line with results from previous studies on the relationship between MSs and ROA (Bart 1997b, Bartkus et al 2006, Hirota et al 2010. As for the relationship between MSs and ROE, to the best of the authors' knowledge, this is the first study to analyze this relationship.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, several studies have found both positive perceptions by CEOs (Analoui and Karami 2002) and a measurably positive relationship between MS comprehensiveness (e.g., by integrating several components of Pearce's (1982) framework) and performance in several regions and countries such as US, Japan, and Europe (Bartkus et al 2000, Hirota et al 2010, Sidhu 2003, Williams 2008. In the case of Turkish small and medium-sized enterprises (SMEs), Duygulu et al (2016) concluded that three of Pearce's (1982) MS components (i.e., survival, growth, and profit; philosophy and value; and public image) served as independent variables that explained high levels of organizational performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sidhu (2003), in his study of firms competing in the dynamic Dutch multi-media industry, found that complete mission statements correlated with exceptional performance. Likewise, while studying Japanese firms, Hirota et al (2010) found empirical evidence for a positive relationship between mission statements and firm performance and between mission statements Reinvigorating the mission statement and desired organizational behavior. Other studies have also provided evidence of a positive relationship between mission statements and desired organizational behaviors (Bart, 1997a;Bart and Baetz, 1998;Bart et al, 2001;Desmidt et al, 2011).…”
Section: The Relationship Between Mission Statements and Firm Performmentioning
confidence: 98%
“…The vision and mission elements could be used as part of an illustrative strategy, as this IM strategy focuses on the organisation's wider purpose and aims, and these can be encapsulated in the organisation's vision and mission (Hirota, Kubo, Miyajima, Hong and Park, 2010;Verma, 2009Verma, -2010. The demonstrative and illustrative strategies could influence audiences' perceptions by informing them about key aspects of the corporate brand, in terms of both specific activities and its broader purpose, although these strategies have not been explored so much in the literature as the assertive and defensive strategies.…”
Section: Im Strategymentioning
confidence: 99%